HOW A RESEARCH ARTICLE INTRUDUCTION STRUCTURED? THE ANALYSIS OF SWALES MODEL (CARS) ON ENGLISH RESEARCH ARTICLE INTRODUCTIONS - Qamariah, Hijjatul; Wahyuni, Sri (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
Research article has been regarded as the most valuable tool in spreading and disseminating research findings around the globe. Knowledge and new information are easily obtained through research articles. However, writing a research article is not easy. Several requirements need to be fulfilled in order to be accepted by the publisher. The weakness of research articles that make those are rejected by the publisher is believed because the papers lack of establishing a territory of the topic discussed and showing the publisher that the paper proposed is worthy enough to be accepted. The essential part of the article is not announced clearly, the gaps that other articles or pervious researches fail to address are not filled. Thus, the article is merely announcing the description of the research but it is not worth to be published in a good journal. One of ways to solve the problem is by writing a good introduction. The most prominent part of a research article is the introduction where the author shows the core point of his research article deserves publishersâ attention. The well known and accepted model of article introduction structure is Swales model know as CARS (Create a Research Space). This model has been believed as a typical way a research article introduction structured around the globe. Therefore, this study tried to portray the way how a research article introduction written based on the common convention of good article introduction. The procedure of how the article introduction structured based on Swales Model is pictured. And some English research article introductions written is analyzed to show the organization of Swales model research article introduction. It is hoped that this study can provide a solution for writers especially novice writers to write a good research article introduction.Â Keywords: Research Article Introduction, Swales Model, CARS